Social Media in Rural China Social Networks and Moral Frameworks - McDonald, Tom (Why We Post, 2016)
China's distinctive social media platforms have gained notable popularity among the nation's vast number of internet users, but has China's countryside been 'left behind' in this communication revolution? Tom McDonald spent 15 months living in a small rural Chinese community researching how the residents use social media in their daily lives. His ethnographic findings suggest that, far from being left behind, social media is already deeply integrated into the everyday experience of many rural Chinese people.